Involvement of Central β-Adrenergic Circuitry in Food and Water Intake in Chickens - Baghbanzadeh, A.; Hamidiya, Z.; Geranmayeh, M.H. (Нейрофизиология, 2015)
We examined the effects of intracerebroventricular (i.c.v.) microinjections of α, β-adrenergic agonist, isoproterenol (ISOP), and of a β₁,₂-adrenoceptor blocker, propranolol (PROP), on food and water intake in broiler cockerels deprived of food and water for 3 h. We found that ISOP, at a 200 nM concentration and not smaller, significantly (P ≤ 0.05) increased food intake but not water intake. PROP microinjected in different doses (20-80 mM) significantly (P ≤ 0.05) decreased food intake. These observation suggest a direct orexigenic role for the β₁ - and β-adrenergic systems in the regulation of food intake in chickens. The significant (P ≤ 0.05) effect of i.c.v. injections of PROP (transient increase in water intake) implies a role of the adrenergic system, possibly via α-adrenoceptors, in the regulation of water intake in broilers, which is food intake-independent.